Involvement of distinct PKC gene products in T cell functions - Baier, Gottfried; Pfeifhofer, Christa; Thuille, Nikolaus (Frontiers in Immunology, 2012)
It is well established that members of the protein kinase C (PKC) family seem to have important roles in T cells. Focusing on the physiological and non-redundant PKC functions established in primary mouse T cells via germline gene-targeting approaches, our current knowledge defines two particularly critical PKC gene products, PKCθ and PKCα, as the “flavor of PKC” in T cells that appear to have a positive role in signaling pathways that are necessary for full antigen receptor-mediated T cell activation ex vivo and T cell-mediated immunity in vivo. Consistently, in spite of the current dogma that PKCθ inhibition might be sufficient to achieve complete immunosuppressive effects, more recent results have indicated that the pharmacological inhibition of PKCθ, and additionally, at least PKCα, appears to be needed to provide a successful approach for the prevention of allograft rejection and treatment of autoimmune diseases.